IMPLEMENTASI DEEP LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM - Ahmad Asroni (Jurnal Manajemen Pendidikan, 2026)
This article aims to critically examine the concept of deep learning and its significance, urgency, and implementation in Islamic Religious Education (IRE) at public universities, including the associated challenges and pedagogical implications. This study employs library research design. Data were collected through a critical review of primary and secondary sources, including academic books and journal articles addressing deep learning, higher education pedagogy, and contemporary Islamic education. The findings indicate that deep learning represents a relevant and strategic pedagogical approach in IRE, as it is capable of holistically integrating cognitive, affective, and ethical dimensions of learning. The implementation of deep learning through problem-based learning, critical-reflective discussions, and the utilization of digital technologies contribute to the enhancement of IRE learning quality, making it more meaningful, contextual, and transformative. Despite facing structural, cultural, and pedagogical challenges, this approach demonstrates significant implications for strengthening students’ character development, ethical awareness, and religious moderation. The novelty of this article lies in its conceptual integration of the deep learning paradigm in higher education with the normative–substantive objectives of Islamic Religious Education in public universities, thereby offering an alternative pedagogical framework that is relevant to the Islamic context and the challenges of modern education.